Preparation method of impact-resistant, high-hardness and heat-resistant N, Cu-CQDs-coated Fe-PTA MOF / WEP anticorrosive paint and coating

By dispersing the modified Fe-PTA MOF and N,Cu-CQDs into the aqueous epoxy resin to form N,Cu-CQDs@Fe-PTA MOF/WEP anticorrosion coating, the problem of micro-holes and micro-cracks generated during the curing process of the aqueous epoxy resin coating is solved, and the corrosion resistance and mechanical properties of the coating are significantly improved.

CN119842292APending Publication Date: 2025-04-18JILIN POWER SUPPLY COMPANY STATE GRID JILIN ELECTRIC POWER +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510144509.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing aqueous epoxy resin coatings are prone to micropores and microcracks during the curing process, which cannot effectively protect against corrosive media, and lack methods to improve the micropores and cracks of the coating.

Method used

By dispersing the modified iron-based metal-organic framework (Fe-PTA MOF) and nitrogen and copper-codoped carbon quantum dots (N,Cu-CQDs) into the aqueous epoxy resin, an impact-resistant, high hardness and heat-resistant N,Cu-CQDs@Fe-PTA MOF/WEP anticorrosion coating is formed.

Benefits of technology

It significantly improves the heat, wear and impact resistance of the coating, and enhances the oxidation and corrosion resistance, extends the service life of the coating, while ensuring the environmental friendliness of the material and low preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842292A_ABST
    Figure CN119842292A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an impact-resistant, high-hardness and heat-resistant N, Cu-CQDs (at) Fe-PTA MOF / WEP anticorrosive coating and a coating, relates to the field of anticorrosive coatings, and aims to solve the problem that a method for improving micropores and cracks of a water-borne epoxy resin coating by taking modified MOF and CQDs as fillers is lacked in the prior art. Comprising the following steps: (1) mixing a FeCl3-DMF (Dimethyl Formamide) solution and a terephthalic acid-DMF solution for hydrothermal reaction, centrifuging, washing and drying to obtain Fe-PTA MOF; (2) ultrasonically mixing citric acid, EDTA-2Na and Cu (NO3) 2 in ethanol to obtain a mixed solution A, performing hydrothermal reaction on the mixed solution A, filtering, further separating small molecular impurities, and performing vacuum freeze drying to obtain N, Cu-CQDs; and (3) N, Cu-CQDs and Fe-PTA MOF are added into deionized water to obtain an N, Cu-CQDs solution and a Fe-PTA MOF solution, the N, Cu-CQDs solution and the Fe-PTA MOF solution are mixed to obtain a mixed solution B, the mixed solution B is stirred overnight, solids are collected and dried, and N, Cu-CQDs-coated Fe-PTA MOF powder is obtained. And (4) adding the N, Cu-CQDs (at) Fe-PTA MOF into epoxy resin, uniformly mixing, and then adding an auxiliary agent to obtain the N, Cu-CQDs (at) Fe-PTA MOF / WEP anticorrosive coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-corrosion coatings, and in particular to a preparation method and coating of an impact-resistant, high-hardness, and heat-resistant N,Cu-CQDs@Fe-PTA MOF / WEP anti-corrosion coating. Background Art

[0002] Steel is an important support for the national economy, infrastructure and other fields, but the problem of metal corrosion cannot be ignored, and metal corrosion causes huge economic losses. Coating anti-corrosion coatings on metal surfaces is a simple, economical and efficient anti-corrosion method to prevent direct contact between corrosive media and metals. Waterborne epoxy resin (WEP) is an organic polymer coating with low volatility, high adhesion and good chemical stability. It has been widely used in marine engineering, bridges, construction and other fields. Although a single WEP has a certain barrier effect on corrosive media, it is easy to produce micropores and microcracks during curing and cannot play a long-term protective role. Adding fillers to WEP can make up for these micropores and cracks. Organic frameworks (MOFs) are porous crystalline nanomaterials composed of various metal ions along organic ligands. Due to their cage-like structure, large surface area and functional adjustability, they are increasingly used in the preparation of coatings; however, MOFs have poor anti-corrosion and mechanical properties, and MOFs need to be modified. Carbon quantum dots (CQDs) not only have good optical and physical and chemical properties of semiconductors, but also have the advantages of high stability, simple synthesis, and abundant precursors. However, CQDs are difficult to separate by centrifugation and have poor stability, so they need to be modified and modified. Dispersing the modified MOF and CQDs together in waterborne epoxy resin is expected to enhance the anticorrosion and mechanical properties of WEP.

[0003] In summary, the existing water-based epoxy resins need to be further improved and developed. Summary of the invention

[0004] The technical problems to be solved by the present invention are:

[0005] The prior art lacks a method for improving the micropores and cracks of waterborne epoxy resin coatings by using modified MOFs and CQDs as fillers.

[0006] The present invention adopts the following technical solutions to solve the above technical problems:

[0007] The present invention provides a method for preparing an impact-resistant, high-hardness, and heat-resistant N,Cu-CQDs@Fe-PTA MOF / WEP anticorrosion coating, comprising the following steps:

[0008] (1) mixing a FeCl3-DMF solution and a terephthalic acid-DMF solution for hydrothermal reaction, and after the reaction, centrifuging, washing, and drying to obtain Fe-PTA MOF;

[0009] (2) ultrasonically mixing citric acid, EDTA-2Na and Cu(NO3)2 into ethanol to obtain a mixed solution A, subjecting the mixed solution A to a hydrothermal reaction, filtering after the reaction, further separating small molecular impurities, and finally freeze-drying under vacuum to obtain N,Cu-CQDs;

[0010] (3) N,Cu-CQDs and Fe-PTA MOF were added into deionized water respectively to obtain N,Cu-CQDs solution and Fe-PTA MOF solution, and the N,Cu-CQDs solution and Fe-PTA MOF solution were mixed to obtain mixed solution B, which was stirred overnight. The solid was collected and dried to obtain N,Cu-CQDs@Fe-PTA MOF powder.

[0011] (4) Add N,Cu-CQDs@Fe-PTA MOF to epoxy resin, mix evenly, and then add additives to obtain N,Cu-CQDs@Fe-PTA MOF / WEP anticorrosion coating.

[0012] Furthermore, the FeCl3-DMF solution in step (1) is prepared by adding (1-2) g FeCl3.6H2O to every 10 mL DMF.

[0013] Furthermore, the terephthalic acid-DMF solution in step (1) is prepared by adding (0.4-1) g of terephthalic acid per 30 mL of DMF.

[0014] Furthermore, the hydrothermal reaction conditions in step (1) are a temperature of 100° C. to 130° C. and a time of 20 h to 24 h.

[0015] Furthermore, in step (2), the mass ratio of citric acid, EDTA-2Na and Cu(NO3)2 is (2-6):(5-10):(1-3).

[0016] Furthermore, the conditions of the hydrothermal reaction in step (2) are a temperature of 180 to 200° C. and a time of 8 to 12 hours.

[0017] Furthermore, in step (3), the concentration of the N,Cu-CQDs solution is (6-10) mg / mL, and the concentration of the Fe-PTA MOF solution is (3-6) mg / mL. The N,Cu-CQDs solution and the Fe-PTA MOF solution are mixed in equal volumes to obtain a mixed solution B.

[0018] Furthermore, in step (4), the mass ratio of N,Cu-CQDs@Fe-PTAMOF to epoxy resin is (1-5):10.

[0019] The present invention provides an impact-resistant, high-hardness, heat-resistant and anti-corrosion coating, wherein the anti-corrosion coating is formed by the anti-corrosion coating described in any one of the above technical solutions.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The iron-based terephthalate metal-organic framework (Fe-PTAMOF) of the present invention has adjustable internal surface characteristics and excellent thermal stability, which helps to improve the physical properties of the material. Its inorganic and organic mixed characteristics make it highly compatible with the polymer matrix; the nitrogen and copper co-doped carbon quantum dots (N, Cu-CQDs) of the present invention, sp2 hybridized conjugated carbon cores and shells containing functional groups such as -COOH, -NH and -OH provide additional functionalization potential; the present invention encapsulates N, Cu-CQDs in Fe-PTAMOF, and the compact heterogeneous structure between the two exhibits obvious synergistic effects when combined, which can enhance the stability and functionality while maintaining its original form unchanged; a stable network structure is formed by cross-linking between organic matter and epoxy resin, which improves the heat resistance, wear resistance, impact resistance, oxidation resistance and corrosion resistance of the coating, and enhances the coating's service life.

[0022] The Fe-PTA MOF of the invention is environmentally friendly and has low preparation cost. The N, Cu-CQDs have the advantages of simple synthesis method, strong antioxidant and antibacterial ability, low toxicity, fluorescence, etc. The prepared coating has a simple preparation process, is non-toxic, and has good anti-corrosion performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a Fourier transform infrared spectrum (FTIR) diagram of N,Cu-CQDs@Fe-PTA MOF in the embodiment of the present invention;

[0024] Figure 2 It is a Raman spectrum (Raman) diagram of N,Cu-CQDs@Fe-PTA MOF in the embodiment of the present invention;

[0025] Figure 3 This is an EIS comparison diagram of N,Cu-CQDs@Fe-PTA MOF / WEP coating in an embodiment of the present invention;

[0026] Figure 4 This is a thermogravimetric analysis diagram of the N,Cu-CQDs@Fe-PTA MOF / WEP coating in an embodiment of the present invention;

[0027] Figure 5 This is a physical indicator diagram of the N,Cu-CQDs@Fe-PTA MOF / WEP coating in an embodiment of the present invention. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the scheme of the present invention, exemplary implementations or embodiments of the present invention will be described below in conjunction with the accompanying drawings. Obviously, the described implementations or embodiments are only implementations or embodiments of a part of the present invention, not all of them. Based on the implementations or embodiments of the present invention, all other implementations or embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present invention.

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0030] In a typical embodiment of the present invention, a method for preparing an impact-resistant, high-hardness, and heat-resistant N,Cu-CQDs@Fe-PTA MOF / WEP anticorrosion coating is provided, comprising the following steps:

[0031] (1) Fe-PTA MOF material was prepared by solvothermal method;

[0032] ① Add FeCl3.6H2O into DMF, stir and dissolve thoroughly to obtain FeCl3-DMF solution;

[0033] ② Add terephthalic acid into DMF, stir thoroughly to dissolve, and obtain terephthalic acid-DMF solution;

[0034] ③ The FeCl3-DMF solution and the terephthalic acid-DMF solution are mixed for hydrothermal reaction. After the reaction is completed, centrifugation, washing and drying are performed to obtain Fe-PTA MOF;

[0035] (2) Preparation of N,Cu-CQDs by hydrothermal method;

[0036] ①Ultrasonically mix citric acid, EDTA-2Na and Cu(NO3)2 in ethanol to obtain a mixed solution A;

[0037] ② The mixed solution A is subjected to a hydrothermal reaction, filtered after the reaction is completed, and the filtrate is dialyzed with a dialysis bag to separate small molecular impurities; and then freeze-dried under vacuum to obtain N,Cu-CQDs;

[0038] (3) Preparation of functional N,Cu-CQDs@Fe-PTA MOF;

[0039] ① N,Cu-CQDs and Fe-PTA MOF were added to deionized water to obtain N,Cu-CQDs solution and Fe-PTAMOF solution, and the N,Cu-CQDs solution and Fe-PTA MOF solution were mixed to obtain mixed solution B, which was stirred overnight to collect N,Cu-CQDs@Fe-PTA MOF solid;

[0040] ② The obtained N,Cu-CQDs@Fe-PTA MOF solid was vacuum dried to obtain N,Cu-CQDs@Fe-PTA MOF powder;

[0041] (4) Preparation of N,Cu-CQDs@Fe-PTA MOF / WEP anticorrosion coating;

[0042] ① Add N,Cu-CQDs@Fe-PTA MOF into epoxy resin, stir thoroughly, and disperse evenly by ultrasound;

[0043] ② Add curing agent and defoaming agent, continue to stir and mix evenly to obtain N,Cu-CQDs@Fe-PTA MOF / WEP anticorrosion coating.

[0044] In a typical embodiment of the present invention, in order to improve the stability of the metal-organic framework, preferably, the FeCl3-DMF solution in step (1)① is prepared by adding (1-2) g FeCl3.6H2O to every 10 mL DMF.

[0045] In a typical embodiment of the present invention, in order to improve the stability of the reaction, preferably, the terephthalic acid-DMF solution in step (1) ② is prepared by adding (0.4-1) g of terephthalic acid per 30 mL of DMF.

[0046] In a typical embodiment of the present invention, preferably, the hydrothermal reaction conditions in step (1) ③ are a temperature of 100° C. to 130° C. and a time of 20 h to 24 h.

[0047] In a typical embodiment of the present invention, preferably, the drying conditions in step (1) ③ are: temperature of 60° C. to 80° C. and time of 10 h to 12 h.

[0048] In a typical embodiment of the present invention, preferably, in step (2)①, the mass ratio of citric acid, EDTA-2Na and Cu(NO3)2 is (2-6):(5-10):(1-3).

[0049] In a typical embodiment of the present invention, preferably, the conditions of the hydrothermal reaction in step (2) ② are a temperature of 180 to 200° C. and a time of 8 to 12 hours.

[0050] In a typical embodiment of the present invention, in order to fully remove macromolecules and improve material purity, preferably, the dialysis time in step (2) ② is 24 h to 36 h, and the deionized water is replaced every 6 h.

[0051] In a typical embodiment of the present invention, in order to make the metal-organic framework have a better coating effect on carbon quantum dots and stronger stability, preferably, the concentration of the N,Cu-CQDs solution in step (3)① is (6-10) mg / mL, and the concentration of the Fe-PTAMOF solution is (3-6) mg / mL. The N,Cu-CQDs solution and the Fe-PTA MOF solution are mixed in equal volumes to obtain a mixed solution B.

[0052] In a typical embodiment of the present invention, preferably, the mass ratio of N,Cu-CQDs@Fe-PTA MOF to epoxy resin in step (4)① is (1-5):10.

[0053] The beneficial effects of the present invention will be described below in conjunction with specific embodiments and comparative examples.

[0054] Example 1

[0055] (1) A new Fe-PTA MOF material was prepared by solvothermal method;

[0056] ① Add 1.5 g FeCl3.6H2O to 10 mL DMF (dimethylformamide) and stir for 5 min to fully dissolve the solute to obtain FeCl3-DMF solution.

[0057] ② Add 0.4 g PTA (terephthalic acid) into 30 mL DMF and stir thoroughly to dissolve it gradually to obtain a terephthalic acid-DMF solution;

[0058] ③ The FeCl3-DMF solution and the terephthalic acid-DMF solution were slowly mixed and reacted in an autoclave reactor at 110°C for 20 hours; after the reaction vessel was cooled to room temperature, centrifuged, and the precipitate was washed three times with ethanol, and dried at 60°C under vacuum atmosphere for 12 hours to obtain Fe-PTA MOF.

[0059] (2) Preparation of N,Cu-CQDs materials using hydrothermal method;

[0060] ① Ultrasonic mixing of 2 g citric acid, 5 g EDTA-2Na and 1 g Cu(NO3)2 in 160 mL ethanol to obtain a mixed solution A;

[0061] ② Transfer the mixed solution A to a polytetrafluoroethylene-lined high-pressure reactor, heat it at 200°C for 10 hours, cool it naturally, and filter it using filter paper and a microfiltration membrane (pore size 0.22 μm); transfer the filtrate to a dialysis bag and dialyze it for 36 hours to separate small molecular impurities, and replace the deionized water every 6 hours; freeze-dry and dehydrate it under vacuum to obtain N,Cu-CQDs.

[0062] (3) Preparation of functional N,Cu-CQDs@Fe-PTA MOF hybrids;

[0063] ① Add N,Cu-CQDs to deionized water to prepare (50 mL; 6 mg / mL) N,Cu-CQDs solution, and add Fe-PTA MOF to deionized water to prepare (50 mL; 3 mg / mL) Fe-PTA MOF solution; N,Cu-CQDs solution and Fe-PTA MOF solution are mixed to obtain mixed solution B, and mixed solution B is stirred at 25°C overnight; then, the water is evaporated, centrifuged, and N,Cu-CQDs@Fe-PTAMOF solid is collected.

[0064] ② Dry the N,Cu-CQDs@Fe-PTA MOF solid in vacuum at 70°C for 12 h to obtain N,Cu-CQDs@Fe-PTAMOF powder.

[0065] (4) Preparation of N,Cu-CQDs@Fe-PTA MOF / WEP anticorrosion coating;

[0066] ① Weigh 1g N, Cu-CQDs@Fe-PTA MOF, add it to 10g epoxy resin, stir it thoroughly, and then perform ultrasonic dispersion to make it evenly dispersed in the epoxy resin;

[0067] ② Add 10 g of curing agent and 1 ml of defoaming agent, and continue stirring until evenly mixed to obtain N,Cu-CQDs@Fe-PTAMOF / WEP anti-corrosion coating, and apply the N,Cu-CQDs@Fe-PTA MOF / WEP anti-corrosion coating to Q235 steel sheet to form a N,Cu-CQDs@Fe-PTA MOF / WEP coating with a thickness of 0.5 mm.

[0068] Example 2

[0069] The difference between this embodiment and embodiment 1 is that:

[0070] In step (1) ②, 0.8 g of PTA was added to 30 mL of DMF and stirred thoroughly to dissolve it gradually, thereby obtaining a terephthalic acid-DMF solution.

[0071] Example 3

[0072] The difference between this embodiment and embodiment 1 is that:

[0073] In step (1) ②, 1 g of PTA is added to 30 mL of DMF and stirred thoroughly to dissolve it gradually, thereby obtaining a terephthalic acid-DMF solution.

[0074] Example 4

[0075] The difference between this embodiment and embodiment 1 is that:

[0076] In step (2) ②, the mixed solution A is transferred to a polytetrafluoroethylene-lined high-pressure reactor, heated at 180°C for 8 hours, cooled naturally, and filtered using filter paper and a microfiltration membrane (pore size 0.22 μm); the filtrate is transferred to a dialysis bag and dialyzed for 36 hours to separate small molecular impurities, and the deionized water is replaced every 6 hours; freeze-drying and dehydration are performed under vacuum to obtain N,Cu-CQDs.

[0077] Example 5

[0078] The difference between this embodiment and embodiment 4 is that:

[0079] In step (2)①, 4 g of citric acid, 8 g of EDTA-2Na and 2 g of Cu(NO3)2 are ultrasonically mixed in 160 mL of ethanol to obtain a mixed solution A.

[0080] Example 6

[0081] The difference between this embodiment and embodiment 4 is that:

[0082] Step (2) comprises: ① ultrasonically mixing 6 g of citric acid, 10 g of EDTA-2Na and 3 g of Cu(NO3)2 in 160 mL of ethanol to obtain a mixed solution A.

[0083] ② Transfer the mixed solution A to a polytetrafluoroethylene-lined high-pressure reactor, heat it at 200°C for 12 hours, cool it naturally, and filter it using filter paper and a microfiltration membrane (pore size 0.22 μm); transfer the filtrate to a dialysis bag and dialyze it for 36 hours to separate small molecular impurities, and replace the deionized water every 6 hours; freeze-dry and dehydrate it under vacuum to obtain N,Cu-CQDs.

[0084] Example 7

[0085] The difference between this embodiment and embodiment 1 is that:

[0086] In step (3) ①, N,Cu-CQDs are added to deionized water to prepare (50 mL; 10 mg / mL) N,Cu-CQDs solution, and Fe-PTA MOF is added to deionized water to prepare (50 mL; 6 mg / mL) Fe-PTA MOF solution; the N,Cu-CQDs solution and the Fe-PTAMOF solution are mixed to obtain a mixed solution B, and the mixed solution B is stirred at 25°C overnight; then, the water is evaporated, centrifuged, and the N,Cu-CQDs@Fe-PTA MOF solid is collected.

[0087] Example 8

[0088] The difference between this embodiment and embodiment 1 is that:

[0089] In step (3) ①, N,Cu-CQDs are added to deionized water to prepare (50 mL; 6 mg / mL) N,Cu-CQDs solution, and Fe-PTA MOF is added to deionized water to prepare (50 mL; 6 mg / mL) Fe-PTA MOF solution; the N,Cu-CQDs solution and the Fe-PTAMOF solution are mixed to obtain a mixed solution B, and the mixed solution B is stirred at 25°C overnight; then, the water is evaporated, centrifuged, and the N,Cu-CQDs@Fe-PTA MOF solid is collected.

[0090] Example 9

[0091] The difference between this embodiment and embodiment 1 is that:

[0092] In step (3) ①, N,Cu-CQDs are added to deionized water to prepare (50 mL; 10 mg / mL) N,Cu-CQDs solution, and Fe-PTA MOF is added to deionized water to prepare (50 mL; 3 mg / mL) Fe-PTA MOF solution; the N,Cu-CQDs solution and the Fe-PTAMOF solution are mixed to obtain a mixed solution B, and the mixed solution B is stirred at 25°C overnight; then, the water is evaporated, centrifuged, and the N,Cu-CQDs@Fe-PTA MOF solid is collected.

[0093] Example 10

[0094] The difference between this embodiment and embodiment 1 is that:

[0095] In step (4) ①, ① weigh 2 g N, Cu-CQDs@Fe-PTAMOF, add it to 10 g epoxy resin, stir it thoroughly, and then perform ultrasonic dispersion to evenly disperse it in the epoxy resin;

[0096] ② Add 10 g of curing agent and 1 ml of defoaming agent, and continue stirring until evenly mixed to obtain N,Cu-CQDs@Fe-PTAMOF / WEP anti-corrosion coating, and apply the N,Cu-CQDs@Fe-PTA MOF / WEP anti-corrosion coating to Q235 steel sheet to form a N,Cu-CQDs@Fe-PTA MOF / WEP coating with a thickness of 0.5 mm.

[0097] Embodiment 11

[0098] The difference between this embodiment and embodiment 1 is that:

[0099] ① Weigh 3g N, Cu-CQDs@Fe-PTA MOF, add it to 10g epoxy resin, stir it thoroughly, and then perform ultrasonic dispersion to make it evenly dispersed in the epoxy resin.

[0100] Example 12

[0101] The difference between this embodiment and embodiment 1 is that:

[0102] ① Weigh 5 g N, Cu-CQDs@Fe-PTA MOF, add it to 10 g epoxy resin, stir it thoroughly, and then perform ultrasonic dispersion to make it evenly dispersed in the epoxy resin.

[0103] Comparative Example 1

[0104] Weigh 10 g of epoxy resin, add 10 g of curing agent and 1 ml of defoaming agent, and continue stirring until evenly mixed to obtain a WEP anti-corrosion coating. Apply the WEP anti-corrosion coating to a Q235 steel sheet to form a WEP coating with a thickness of 0.5 mm.

[0105] Comparative Example 2

[0106] The difference between this embodiment and embodiment 1 is that:

[0107] ① Weigh 1g of Fe-PTA MOF, add it to 10g of epoxy resin, stir thoroughly, and then perform ultrasonic dispersion to evenly disperse it in the epoxy resin.

[0108] ② Add 10 g of curing agent and 1 ml of defoaming agent, continue stirring until evenly mixed to obtain a Fe-PTA MOF / WEP anti-corrosion coating, and apply the Fe-PTA MOF / WEP anti-corrosion coating to a Q235 steel sheet to form a Fe-PTA MOF / WEP coating with a thickness of 0.5 mm.

[0109] The N, Cu-CQDs@Fe-PTA MOF and Fe-PTA MOF materials synthesized in Example 1 were subjected to infrared spectroscopy and Raman spectroscopy. Figure 1 As shown, located at about 3200-3600cm-1 The peak at 1750 cm-1 in the Fe-PTA MOF spectrum is attributed to the stretching mode of the hydroxyl groups within the MOF structure. -1 The band at 1555 cm -1 and 1391cm -1 The peaks at 1521 cm -1 The peak observed at 749 cm -1 The absorption band of 1296cm is related to the bending vibration of CH bond. -1 The bands at 2763-2905 and 1278 cm-1 are related to the stretching vibration of Fe-O, indicating the successful formation of MOF nanostructures. -1 The characteristic peaks at 3200-3600 cm-1 are attributed to the CH vibration and CN stretching of sp2 or sp3 hybridized carbon, respectively. -1 (hydroxyl) and 1643cm -1 The peak intensity near the (carboxyl) group is enhanced. The FTIR spectrum of Cu doping shows a strong peak in the metal sensitive region (1080 cm -1 -990cm -1 ) N-Cu-N bonds appeared, indicating that N and Cu were successfully doped in CQDs. The changes in the surface functional groups of N,Cu-CQDs@Fe-PTA MOF particles were attributed to the presence of hydroxyl, carboxyl or amine groups on the surface of synthesized N,Cu-CQDs, indicating that MOF has encapsulated N,Cu-CQDs. In the Raman spectrum ( Figure 2 ), the characteristic peaks corresponding to Fe-PTA MOF and N,Cu-CQDs@Fe-PTA MOF were observed, indicating that the chemical reaction successfully occurred on the surface of N,Cu-CQDs and Fe-PTA MOF grew on the surface of N,Cu-CQDs. The detection results were consistent with FTIR.

[0110] The N,Cu-CQDs@Fe-PTA MOF / WEP coating of Example 1 and the Fe-PTA MOF / WEP coating of Comparative Example 2 were immersed in a 3.5 wt% NaCl solution. The EIS comparison of the two coatings is shown in FIG. Figure 3 As shown in Figure 2, on the first day of immersion, the impedance modulus of the N,Cu-CQDs@Fe-PTA MOF / WEP coating was 8.3×10 7 Ω·cm 2 The impedance modulus of Fe-PTA MOF / WEP coating is 7.5×10 7 Ω·cm 2At the end of immersion, the impedance modulus of Cu-CQDs@Fe-PTA MOF / WEP coating was 2.6×10 7 Ω·cm 2 , while the impedance modulus of Fe-PTA MOF / WEP coating is 1.8×10 7 Ω·cm 2 During the entire immersion process, the impedance modulus of the N,Cu-CQDs@Fe-PTA MOF / WEP coating is always higher than that of the Fe-PTA MOF / WEP coating. Therefore, N,Cu-CQDs@Fe-PTAMOF can more effectively improve the anti-corrosion performance of the coating and have a longer protective effect. In order to clarify the thermal stability of N,Cu-CQDs@Fe-PTA MOF / WEP at high temperatures, thermogravimetric TG tests were performed, such as Figure 4 The results shown in the figure show that at 300°C, the weight loss of N,Cu-CQDs@Fe-PTA MOF / WEP is low (lower than 5.4% of Fe-PTA MOF / WEP). When the temperature reaches 400°C, the mass loss of N,Cu-CQDs@Fe-PTAMOF / WEP is 15.35% less than that of Fe-PTAMOF / WEP; when the temperature reaches 800°C, N,Cu-CQDs@Fe-PTAMOF / WEP loses 81.2%, at which time WEP has completely volatilized, indicating that N,Cu-CQDs@Fe-PTA MOF / WEP has good thermal stability.

[0111] The physical properties of the coatings of Example 1 and Comparative Example 1 were tested, and the results are as follows: Figure 5 As shown, combined with the results in Table 1, it can be seen that the physical properties of the N,Cu-CQDs@Fe-PTA MOF / WEP coating of the present invention are significantly better than those of the WEP coating and the Fe-PTA MOF / WEP coating.

[0112] Table 1

[0113]

[0114]

[0115] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing an impact-resistant, high-hardness, heat-resistant N, Cu-CQDs@Fe-PTA MOF / WEP anticorrosion coating, characterized in that: The steps include: (1) mixing a FeCl3-DMF solution and a terephthalic acid-DMF solution for hydrothermal reaction, and after the reaction, centrifuging, washing, and drying to obtain Fe-PTA MOF; (2) ultrasonically mixing citric acid, EDTA-2Na and Cu(NO3)2 in ethanol to obtain a mixed solution A, subjecting the mixed solution A to a hydrothermal reaction, filtering after the reaction, further separating small molecular impurities, and finally freeze-drying under vacuum to obtain N, Cu-CQDs; (3) N, Cu-CQDs and Fe-PTA MOF were added to deionized water respectively to obtain N, Cu-CQDs solution and Fe-PTA MOF solution, and the N, Cu-CQDs solution and Fe-PTA MOF solution were mixed to obtain a mixed solution B, which was stirred overnight. The solid was collected and dried to obtain N, Cu-CQDs@Fe-PTA MOF powder. (4) Add N, Cu-CQDs@Fe-PTA MOF to epoxy resin, mix well, and then add additives to obtain N, Cu-CQDs@Fe-PTA MOF / WEP anticorrosion coating.

2. The method for preparing the impact-resistant, high-hardness, heat-resistant N, Cu-CQDs@Fe-PTA MOF / WEP anticorrosion coating according to claim 1, characterized in that: The FeCl3-DMF solution in step (1) is prepared by adding (1-2) g FeCl3.6H2O to every 10 mL DMF.

3. The method for preparing the impact-resistant, high-hardness, heat-resistant N, Cu-CQDs@Fe-PTA MOF / WEP anticorrosion coating according to claim 2, characterized in that: The terephthalic acid-DMF solution in step (1) is prepared by adding (0.4-1) g of terephthalic acid per 30 mL of DMF.

4. The method for preparing the impact-resistant, high-hardness, heat-resistant N, Cu-CQDs@Fe-PTA MOF / WEP anticorrosion coating according to claim 3, characterized in that: The hydrothermal reaction conditions in step (1) are a temperature of 100° C. to 130° C. and a time of 20 h to 24 h.

5. The method for preparing the impact-resistant, high-hardness, heat-resistant N, Cu-CQDs@Fe-PTA MOF / WEP anticorrosion coating according to claim 4, characterized in that: In step (2), the mass ratio of citric acid, EDTA-2Na and Cu(NO3)2 is (2-6):(5-10):(1-3).

6. The method for preparing the impact-resistant, high-hardness, heat-resistant N, Cu-CQDs@Fe-PTA MOF / WEP anticorrosion coating according to claim 5, characterized in that: The conditions of the hydrothermal reaction in step (2) are a temperature of 180 to 200° C. and a time of 8 to 12 hours.

7. The method for preparing the impact-resistant, high-hardness, heat-resistant N, Cu-CQDs@Fe-PTA MOF / WEP anticorrosive coating according to claim 1, characterized in that: In step (3), the concentration of N, Cu-CQDs solution is (6-10) mg / mL, and the concentration of Fe-PTA MOF solution is (3-6) mg / mL. N, Cu-CQDs solution and Fe-PTAMOF solution are mixed in equal volumes to obtain a mixed solution B.

8. The method for preparing the impact-resistant, high-hardness, heat-resistant N, Cu-CQDs@Fe-PTA MOF / WEP anticorrosion coating according to claim 6 or 7, characterized in that: In step (4), the mass ratio of N, Cu-CQDs@Fe-PTA MOF and epoxy resin is (1-5):

10.

9. An impact-resistant, high-hardness, heat-resistant, anti-corrosion coating, wherein the anti-corrosion coating is formed by the anti-corrosion coating according to any one of claims 1 to 8.